Optimization of Skim Milk Based Medium for Biomass Production of Probiotic Lactobacillus Acidophilus ATCC 4356 Using Face Central Composite Design-Response Surface Methodology Approach - Abdulrazzaq, Alaa Imad; Khalil, Khalilah Abd (Journal of Asian Scientific Research, 2022)
The use of commercial media to support probiotic bacterial growth is limited by its cost and off-flavour generated in food products. Thus, this study optimized skim milk and yeast extract concentration as a cultivation medium for optimal Lactobacillus acidophilus ATCC 4356 biomasses using FCCD-RSM. The statistical analysis showed that the optimal compositions of skim milk and yeast extract were at 9.46 g/L and 1.07 g/L, respectively by setting the goal of optimization for biomass production to be at maximum level and the factor concentration in selected range. Besides, pH profiling showed pH value declined from 4.262 to 4.061 during cultivation due to organic acid produced from carbohydrate metabolism at the predicted response in optimal conditions (0.979 OD600) generated by the RSM tool. However, the experimental and predicted results were not significant difference (P>0.05) with low error percentage. As conclusion, the optimized skim milk (10g/L) and yeast extract (1g/L) obtained from RSM model and experimental values can be used to support better biomass production for L. acidophilus and prepare the cells for further application.